THE INFLUENCE OF WORK LIFE BALANCE AND JOB SATISFACTION ON ORGANIZATIONAL COMMITMENT OF TEBING TINGGI POLICE PERSONNEL - Ahmad Rizki Fauzi; Siti Aisyah; Kaiman Turnip (RADJA PUBLIKA, 2023)
This study aims to determine the effect of WLB and Job Satisfaction on Organizational Commitment in Tebing Tinggi Police Police Personnel. The population of this study were 162 police officers from the Tebing Tinggi Police. Sampling of this study by total sampling technique, where the entire population is a sample of 162 people. This research uses quantitative methods. The measurement tools used are the WLB scale, the Job Satisfaction scale and the Organizational Commitment scale. Data analysis using multiple linear regression test. The results of this study indicate that (1) There is an influence of WLB on Organizational Commitment to Police Personnel at the Tebing Tinggi Police Station, where the significance value is 0.000, namely 0.05, so the hypothesis is rejected.